Pengalaman dan Persepsi Pengguna terhadap Layanan BPJS Kesehatan di Kelurahan Sei Agul, Kota Medan - Dicky Kurniawan; Syndi Febriani; Natasyah Nurputri Hrp; Berlianti Berlianti (Institut Nalanda, 2024)
This study evaluates the user experience of BPJS Kesehatan in Sei Agul Village, Medan City, focusing on benefits, challenges, and satisfaction levels with the services. BPJS Kesehatan, as a national health insurance program, aims to provide affordable healthcare access to the community. The findings reveal that many users benefit from BPJS, particularly in reducing healthcare costs. However, challenges such as long queues, complicated administrative processes, and difficulties in obtaining referrals to specialist doctors are commonly encountered. The average user satisfaction with the services is rated at 7/10, though disparities in service quality based on BPJS classes and issues with the claims process remain.This research employs a qualitative method through interviews and observations to explore user experiences. Recommendations include improving queue management systems, increasing medical staff, enhancing public information dissemination, strengthening digital technology, equalizing service quality, and expediting the referral process. These efforts are expected to enhance the overall user experience and satisfaction with BPJS Kesehatan services.